Off-campus student housing preferences conceptual framework / Mohamad Haizam Mohamed Saraf ... [et al.] - Mohamed Saraf, Mohamad Haizam; Mohd, Thuraiya; Sirat, Kamsiah (2014)
The tertiary education in Malaysia has undergone immense changes from the rapid expansion of Higher Educational Institutions (HEIs) for the past four decades. Consequently, this has also led to the high concentrations of students in residential areas those enclaves of university campuses, i.e. studentification. The fact is, not all universities are able to provide adequate student accommodations as the enrolment of students are far greater than the available student. As a result, students who reside off-campus need to find their own place for dwelling. However, the universities do not provide the off campus students with housing that take into considerations of student’s housing preferences. Nowadays, students have their own expectation of how and where they wish to reside. Hence, off-campus students’ housing preferences should be highlighted when developing all higher institutions to provide a safe and good quality of living. This research is an attempt to suggest a conceptual framework of off-campus student housing preferences from the reviews on the literature. This research may contribute to extend the body of knowledge in the area of studentification especially on off-campus students’ housing preferences and a suggested significant input will give much emphasize on the formation of Student Housing Guideline in Malaysia context.